2017
DOI: 10.3892/ol.2017.5569
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNA in plasma as a non-invasive biomarker for the recurrence of non-small cell lung cancer

Abstract: Abstract. Predictive biomarkers for the recurrence of non-small cell lung cancer (NSCLC) in patients who have received curative resection are important for cancer treatment. The functional microRNAs (miRNAs/miRs) in the exosomes of plasma and serum samples are of interest as stable and non-invasive biomarkers for recurrence in cancer patients. The aim of the present study was to clarify the usefulness of plasma exosomal miRNAs as biomarkers for the prediction of recurrence in NSCLC following curative resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(107 citation statements)
references
References 31 publications
1
104
0
2
Order By: Relevance
“…Another study reported that elevated levels of plasma exosomal miR-23b-3p, miR-10b-5p, and miR-21-5p were prognostic biomarkers for NSCLC patients [20]. Our group also demonstrated that miR-21 and miR-4257 levels of plasma exosomes are useful biomarkers for diseasefree survival (DFS) of NSCLC patients [21]. However, no published reports have evaluated the prognostic value of exosomal miR-451a, which we selected by miRNA array analysis of early-stage NSCLC (stage IA) patients.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…Another study reported that elevated levels of plasma exosomal miR-23b-3p, miR-10b-5p, and miR-21-5p were prognostic biomarkers for NSCLC patients [20]. Our group also demonstrated that miR-21 and miR-4257 levels of plasma exosomes are useful biomarkers for diseasefree survival (DFS) of NSCLC patients [21]. However, no published reports have evaluated the prognostic value of exosomal miR-451a, which we selected by miRNA array analysis of early-stage NSCLC (stage IA) patients.…”
Section: Introductionmentioning
confidence: 59%
“…Plasma and blood cells were separated by centrifugation at 1,200 g for 15 min at 4 ° C; 1.0 mL of plasma was used for miRNA array analysis, and 500 μL for qRT-PCR. The exosomes of the plasma were purified by the ultracentrifugation method described previously [21,22]. In brief, exosomes were separated by ultracentrifugation at 15,000 g for 70 min at 4 ° C, and the pellets were washed with phosphate-buffered saline and stored at -80 ° C for microarray and qRT-PCR analysis.…”
Section: Purification Of Exosome From Plasmamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, they found that exosomal miR-21 was significantly associated with tumor size and tumor-node-metastasis (TNM) stage and exosomal miR-4257 showed an obvious association with lymphatic invasion, histological type and TNM stage of lung cancer. Additionally, the disease-free survival (DFS) rates of high expression exosomal miR-21 patients were significantly worse than those of low exosomal miR-21 patients, and the DFS rates of patients with high exosomal miR-4257 levels were significantly worse than those with low exosomal miR-4257 levels [29].…”
Section: Exosomal Mirnas As Diagnostic and Predictive Biomarkers In Lmentioning
confidence: 99%